Functional groups and traits in Mediterranean serpentine ecosystems (Sierra Bermeja, Spain). - Hidalgo-Triana, Noelia; Pérez-Latorre, Andrés Vicente; Thorne, James H.; Adomou, Aristide (My University, 2021)
The study of plant functional traits (PFTs) as key drivers of ecosystems. In order to know the principal PFTs of serpentine vegetation in the Iberian Peninsula, we studied the south Iberian ultramafic scrublands to determine functional groups (FG). The two types of scrublands studied were: (a) Halimium atriplicifolium plant community and (b) Cistus populifolius plant community. Different plots were established in the respective communities. PFTs studied were: plant height, renewal bud location, branch type, leaf area (LA), specific leaf area (SLA), leaf hairiness, presence/absence of photosynthetic stems, morphology of root system and seasonality of assimilating organs following global standardized protocols. We used PCA to identify the combination of functional traits with major weights and a neighbor-joining clustering to define functional groups. We obtained a high number of FG (between six to eight optimum number of clusters) relative to the total number of taxa. The functional groups obtained showed that these serpentine scrublands are composed of species with a wide ecological range of functional traits. The majority of the serpentinophytes resulted as: (1) chamaephytes (plants with renewal structures around 60 cm. above the soil) and hemixyle plants (plants with a reduced specific density of stems) and with a reduced plant size in comparison to other Mediterranean ecosystems; (2) with lower SLA due to thicker and/or denser leaves, which contributes to long leaf survival, nutrient retention and protection from desiccation; (3) malacophyllous, hairy and small-sized leaves; (4) dimorphic plants (with two types of branches/leaves depending of the seasonal moment) with partial shedding of leaves during summer-deciduous -seasonally dimorphic species-; and (5) with thickened tap roots and shallow root systems. Studies of PFTs, and specially FG, may be very useful for management of plant species in serpentine ecosystems.
Keywords: Ecosistemas mediterráneos; Bermeja (Sierra, Málaga); Arid and semi arid ecosystems; Functional groups; Serpentine ecosystems; Functional traits